Development of Children's Multiple Intelligences in Islamic Kindergartens - Pulungan, Wardah Arsidah; Rizkina, Rahmi; Warohma, Mawaddah; Hasraini, Lonita; Pasaribu, Rodiyah; Yuliantika, Nanda; Sitorus, Masganti (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2023)
The notion of multiple intelligences posits that intelligence cannot solely be quantified by conventional IQ testing, but rather encompasses diverse and distinct forms of intelligence unique to each individual. This study seeks to investigate the implementation of multiple intelligences at Al-Ikhlas Kindergarten utilising a qualitative research methodology, which encompasses interviews and observations. The research findings indicate that education at Al-Ikhlas Kindergarten facilitates the enhancement of intelligence. Educators design activities aligned with the objectives of fostering multiple intelligences, select suitable learning methodologies, and modify pertinent methods, materials, and resources. The educator executes the learning plan by delivering instructions, facilitating activities, and offering advice to students using interactive learning methodologies. Assessment is conducted by observations and interviews. Al-Ikhlas Kindergarten implements diverse activities to cultivate multiple intelligences, including musical intelligence through singing and instrument play, kinaesthetic intelligence via physical activities like dancing and gymnastics, interpersonal intelligence through collaborative play, and intrapersonal intelligence through patience and individual activities. Planting flowers, cultivating naturalist intelligence by observing the environment and engaging in horticultural activities, and fostering spiritual intelligence through storytelling and memorisation of hijaiyah letters.